The Effectiveness of Group Counseling Program Based on Satier to Reduce the Level of Alexithymia of Abused Women - mahmoud, Baraa rawhi; Momani, Fawwaz Ayoub (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aimed to assess the effectiveness of a counseling program based on the Satir approach in reducing alexithymia levels among abused women. Methods: The study used the experimental approach, and the researchers designed a counseling program based on the Satir approach, consisting of 14 sessions. The Toronto Alexithymia Scale (TAS-20) was developed and used. Results: The study results showed that there were statistically significant differences between the arithmetic means of the experimental and control groups on the alexithymia scale in the post-test, and in favor of the experimental group, indicating the effectiveness of the counseling program. The results also showed that there were no statistically significant differences between the average responses of the experimental group members in follow-up measurement after one month. Conclusions: Raising awareness among families and individuals about the importance of respecting women, their rights, appreciating their status, and the necessity of combating all forms of violence. Developing strategic plans to protect women from all forms of violence in collaboration with civil society institutions. Conducting further experimental studies based on other programs to reduce alexithymia and comparing their results with the current study. Implementing counseling programs involving both spouses together.